Pelaksanaan Pembelajaran Berbasis Proyek (PjBL) dalam Pembelajaran Pendidikan Agama Islam - Fika Rahayu Astuti; Indah Rama Sahara; Gusmaneli Gusmaneli (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to achieve several main objectives in order to overcome the existing problems and improve the effectiveness of PjBL in Islamic Education learning. The research method used in this study is descriptive qualitative research, which aims to understand and describe the implementation of Project-based Learning (PjBL) in the context of Islamic Religious Education (PAI) learning. This research focuses on an in-depth exploration of the experiences and views of educators and learners regarding the implementation of PjBL. The results of this study show that the implementation of Project-based Learning (PjBL) at SMPN 1 Sungai Sariak revealed several key findings. Teacher readiness is a crucial factor in the implementation of PjBL, with the main challenges being concept understanding, pedagogical skills, and limited resources and administrative support. Despite enthusiasm, teachers require ongoing training and improved access to resources. The impact of PjBL on learners' understanding showed improvements in cognitive, affective and psychomotor aspects, strengthening understanding of religious concepts, critical thinking skills, and student motivation and engagement. PjBL also develops 21st century skills such as critical thinking, creativity, collaboration and communication, although challenges related to resources and time remain. Overall, despite significant challenges, PjBL has great potential to improve the quality of learning at SMPN 1 Sungai Sariak with proper support and management.